Authoritarian Neoliberalism and The State of Exception: Reading Kais Saied’s Tunisia Through Agamben’s Biopolitics - Rivai, Aspin Nur Arifin (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2025)
This article examines how Giorgio Agamben's concept of the state of exception is relevant to explaining Tunisia's failure to shift away from authoritarianism. Kais Saied's leadership's use of the state of exception routine is not merely seen as an attempt to expand his power. More deeply, the state of exception represents a normal state for governing every aspect of Tunisian society through authoritarian-neoliberalism discourse. Through an analysis of legal decrees, political speeches, and secondary literature, this study finds that Saied has transformed the emergency situation into normal governance by integrating legality, morality, and security into a permanent form of government. These findings reveal that democracy itself latently legitimizes the state of exception as a paradigm exploited by the privilege-determiners. The state of exception, repeatedly declared by ruling regimes, no longer serves to expand power but rather to ensure the continued regulation of social and physical life. Through the state of exception, authoritarianism infiltrates democracy, arbitrarily suspending the constitutional order and the separation of powers. Saied inherited this normalization only in a more subtle form through the co-optation of parliament, the delegitimization of the opposition, and the fragmentation of progressive political movements in the name of "securitization." Thus, the state of exception is not a suspension of the law, but rather the law itself. From an Agambenian perspective, the article argues that the primordial political relationship is one of abandonment: the state absorbs everyone into its order while simultaneously abandoning them to bare life, rendering Tunisian society a bulwark where violence is inevitable.